Profiling of Active Compounds of Extract Ethanol, n-Hexane, Ethyl Acetate and Fraction Ethanol of Star Anise (Illicium verum Hook. f.) and Determination of Total Flavonoids, Total Phenolics and Their Potential as Antioxidants - Mighfar Syukur; Masitoh Suryaning Prahasiwi; Nurkhasanah; Sapto Yuliani; Yuliana Purwaningsih; Erwin Indriyanti (Science and Technology Indonesia, 2023)
Profiling of chemical compounds on star anise extract and fractions showed the content and looked for active compounds. The main compounds in alkaloids, flavonoids, saponins, phenolics, and triterpenoid forms were identified based on phytochemical screening. FTIR and GC-MS analysis were used to purify the extract and fractions’ main compounds. After analyzing the main components of extract and fractions, a correlation was made between the total phenolic and flavonoid content. The total phenolic content was determined by adding folincalteau complexing solution converted to gallic acid equivalent (GAE), while the total flavonoid content was determined by AlCl3 complexing solution converted to Quercetin Equivalent (QE). The total phenolic yields for extract ethanol, n-hexane fraction, ethyl acetate fraction, and fraction ethanol were obtained at 106.45, 52.30, 93.46, and 148.97 mgGAE/g, respectively. Then the total flavonoid results were 107.45, 58.94, 148.99, 140.01 mgQE/g. The total content of phenolics and flavonoids illustrated the number of active compounds that have a role as free radical scavengers due to their group. Antioxidant activity was tested with 1,1-diphenyl-2-picrylhydrazyl (DPPH) on extracts and fractions, with the best IC50 results obtained in the ethanol fraction 0.416 mg/mL.